2015
DOI: 10.5539/ies.v8n2p128
|View full text |Cite
|
Sign up to set email alerts
|

Problems Faced by Preservice Special Education Teachers in Jordan

Abstract: One of the most important factors in the success of educating children with special needs is the quality of the special education teacher. While teachers are responsible for a plethora of duties, it is important that teacher preparation programs provide adequate training to ensure teachers are well prepared for the teaching profession. However, previous research has found that teachers are not being adequately trained and consequently, they are experiencing problems within the classroom. Therefore, the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…The results showed that there were no statistically significant differences concerning the difficulties of field training concerning the gender variable. These results were consistent with the other studies (e.g., Al-Hiary et al, 2015;Al-Nimie et al, 2010;Hamarsha & Al-Rimawi, 2011;Nazir et al, 2011). These results can be explained by referring to the fact that both males and females were affected by the lock downs and the government measures to face the corona pandemic.…”
Section: Discussion Of the Results Of The Second Questionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that there were no statistically significant differences concerning the difficulties of field training concerning the gender variable. These results were consistent with the other studies (e.g., Al-Hiary et al, 2015;Al-Nimie et al, 2010;Hamarsha & Al-Rimawi, 2011;Nazir et al, 2011). These results can be explained by referring to the fact that both males and females were affected by the lock downs and the government measures to face the corona pandemic.…”
Section: Discussion Of the Results Of The Second Questionsupporting
confidence: 93%
“…Other studies indicated that there are no statistical differences in the difficulties in favour of males (Al-Hwaimel & Al-Sa`oub, 2013). Other studies indicated that no differences in the difficulties based on the gender variable (Al-Nimie et al, 2010;Al-Sharia, 2019;Al-Hiary, Almakanin, & Tabbal, 2015;Hamarsha & Al-Rimawi, 2011;Nazir et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Currently, in Saudi Arabia, the field of special education is developing. A well-planned special education program significantly increased the quality of pre-service special educators (Al-Hiary, Almakanin and Tabbal, 2015). Needless to say, strong preparation programs for pre-service teachers can eliminate many difficulties that future teachers in special education may face.…”
Section: Special Education Teacher Preparation In Saudi Arabiamentioning
confidence: 99%
“…Finally, teachers keep in touch with the parental members of the students who are informed of the activities carried out in LDRR. There are some limitations regarding LDRR in KSA such as shortage in well-trained teachers in LD, lack of teaching materials and teacher's guide (Al-Ahmary, 2010;Al-Hiary, Almakanin, & Tabbal, 2015;Theeb, Muhaidat, & Al-Zboon, 2014;Youssefi, 2014). Furthermore, Al-Zoubi and Abdel Rahman (2016) mentioned that the lack of LDRR teacher guide was the major problem that primary school teachers in KSA faced.…”
Section: Learning Disabilities Resources Room (Ldrr)mentioning
confidence: 99%